Implementasi Pengawasan oleh Panwascam dalam Mencegah Politik Uang di Kecamatan Sadu - Taufik Hidaya; Daud Daud; Erwina Kartika Devi; Haeran Haeran; Siti Fatimah (Journal of Innovative and Creativity, 2025)
This study aims to analyze the implementation and effectiveness of supervision carried out by the District Election Supervisory Committee (Panwascam) in an effort to prevent the practice of money politics in the implementation of elections in Sadu District, East Tanjung Jabung Regency. Money politics is a form of serious violation that can damage the integrity of democracy and hinder the realization of fair and clean elections. The background of this study is the still rampant practice of money politics, especially in areas where the level of political awareness of the community is relatively low. The approach used in this study is a descriptive qualitative approach. Data collection techniques were carried out through in-depth interviews with Panwascam, the community, and village officials, and supplemented by documentation studies and field observations. Data analysis was carried out inductively by referring to the theory of policy implementation and effectiveness of supervision. The results of the study indicate that supervision by Panwascam was carried out through several strategies, including socialization, direct supervision in the field, patrols during quiet periods, and dissemination of information through social media. However, the effectiveness of supervision has not been maximized because it is constrained by the limited number of personnel, low community participation in reporting violations, and a political culture that tends to be permissive towards the practice of money politics.